Difference between revisions of "022 Exam 2 Sample B, Problem 3"

From Math Wiki
Jump to navigation Jump to search
(Created page with "<span class="exam"> Find the derivative: <math style="vertical-align: -18%">f(x) \,=\, 2x^3e^{3x+5}</math>.")
 
 
(7 intermediate revisions by the same user not shown)
Line 1: Line 1:
<span class="exam"> Find the derivative: <math style="vertical-align: -18%">f(x) \,=\, 2x^3e^{3x+5}</math>.
+
<span class="exam"> Find the derivative of <math style="vertical-align: -18%">f(x) \,=\, 2x^3e^{3x+5}</math>.
 +
 
 +
 
 +
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 +
!Foundations: &nbsp;
 +
|-
 +
|This problem requires several advanced rules of differentiation.  In particular, you need
 +
|-
 +
|'''The Chain Rule:''' If <math style="vertical-align: -25%;">f</math> and <math style="vertical-align: -15%;">g</math> are differentiable functions, then
 +
|-
 +
 
 +
|<br>&nbsp;&nbsp;&nbsp;&nbsp; <math>(f\circ g)'(x) = f'(g(x))\cdot g'(x).</math>
 +
|-
 +
|<br>'''The Product Rule:'''  If <math style="vertical-align: -25%;">f</math> and <math style="vertical-align: -15%;">g</math> are differentiable functions, then
 +
|-
 +
|<br>&nbsp;&nbsp;&nbsp;&nbsp; <math>(fg)'(x) = f'(x)\cdot g(x)+f(x)\cdot g'(x).</math>
 +
|-
 +
|Additionally, we will need our power rule for differentiation:
 +
|-
 +
|
 +
::<math style="vertical-align: -21%;">\left(x^n\right)'\,=\,nx^{n-1},</math> for <math style="vertical-align: -25%;">n\neq 0</math>,
 +
|-
 +
|as well as the derivative of the exponential function, <math style="vertical-align: 5%">e^x</math>:
 +
|-
 +
|
 +
::<math>(e^x)'\,=\,e^x.</math>
 +
|<br>
 +
|}
 +
 
 +
&nbsp;'''Solution:'''
 +
 
 +
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 +
!Step 1: &nbsp;
 +
|-
 +
|We need to start by identifying the two functions that are being multiplied together so we can apply the product rule. Let's call <math style="vertical-align: -20%">g(x)\,=\,2x^3,\,</math> and <math style="vertical-align: -20%">\,h(x) \, = \, e^{3x + 5}</math>, so <math style="vertical-align: -20%">f(x)=g(x)\cdot h(x)</math>.
 +
|}
 +
 
 +
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 +
!Step 2: &nbsp;
 +
|-
 +
|We can now apply the advanced techniques.This allows us to see that
 +
|-
 +
|
 +
::<math>\begin{array}{rcl}
 +
f'(x)&=&2(x^3)' e^{3x+5}+2x^3(e^{3x+5})' \\
 +
&=&6x^2e^{3x+5}+2x^3(3e^{3x+5})\\
 +
& = &6x^2e^{3x+5}+6x^3e^{3x+5}.
 +
\end{array}</math>
 +
|}
 +
 
 +
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 +
!Final Answer: &nbsp;
 +
|-
 +
|
 +
::<math>f'(x)\,=\,6x^2e^{3x+5}+6x^3e^{3x+5}.
 +
</math>
 +
|}
 +
 
 +
[[022_Exam_2_Sample_B|'''<u>Return to Sample Exam</u>''']]

Latest revision as of 06:50, 17 May 2015

Find the derivative of .


Foundations:  
This problem requires several advanced rules of differentiation. In particular, you need
The Chain Rule: If and are differentiable functions, then

    

The Product Rule: If and are differentiable functions, then

    
Additionally, we will need our power rule for differentiation:
for ,
as well as the derivative of the exponential function, :

 Solution:

Step 1:  
We need to start by identifying the two functions that are being multiplied together so we can apply the product rule. Let's call and , so .
Step 2:  
We can now apply the advanced techniques.This allows us to see that
Final Answer:  

Return to Sample Exam